Perfil de marcadores sorológicos, salivares e moleculares de Mycobacterium leprae entre contatos intradomiciliares de pacientes com hanseníase - Cabral, Paula Brito e (2012)
Leprosy household contacts are group at high risk of developing the disease. We investigated the presence M. leprae DNA in nasal mucosa and anti-PGL1 serum IgG/IgM and salivary IgA/IgM antibodies from leprosy household contacts (n=135) in two endemic regions, Ceara, Brazil. Good correlation between serum IgM and IgG isotypes was observed both in MB and in PB leprosy household contacts (r = 0.39, p <0.0001). However, their levels were much different (p <0.0001). Among the contacts positive for serum IgM, 74 (87%) were found to be negative for serum IgG. In respect to the salivary antibodies, PB leprosy household contacts showed correlation between IgA and IgM (r = 0.60, p <0.0001); the same was observed in MB leprosy contacts (r = 0.77, p <0.0001). It was observed that in 75.3% of the leprosy household contacts who were positive to serum anti-PGL1, their salivary antibodies were negative. On the other hand, 50% of the leprosy household contact who were negative to serum anti-PGL1 antibodies, their salivary antibodies were positive. M. leprae DNA was found in nasal swab in 9 MB household leprosy contacts (10.6%) and in 3 PB leprosy contacts (6.0%). We concluded that quantitative analysis of serum and salivary anti-PGL1 in leprosy contacts is necessary for mounting strategies to survey subclinical leprosy infections in order to prevent development of the disease.